1983
DOI: 10.1111/j.1471-0528.1983.tb08891.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron requirement in normal pregnancy as assessed by serum ferritin, serum transferrin saturation and erythrocyte protoporphyrin determinations

Abstract: Summary. Serum iron, serum iron‐binding capacity, serum ferritin and erythrocyte protoporphyrin were determined during uncomplicated pregnancy in 45 healthy women; 22 were given oral iron while the others were given a placebo. When iron was not given, 15 out of 23 women had exhausted iron stores and iron deficiency at term, as judged from low serum ferritin, low serum transferrin saturation and high erythrocyte protoporphyrin values. Only seven of them had a haemoglobin concentration between 10 and 11 g/dl at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
101
2
4

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 29 publications
5
101
2
4
Order By: Relevance
“…With respect to the startup values, the only factor that showed a statistically significant increase was serum ironbinding capacity. No statistically significant difference could be determined in other parameters [29]. In the present study, serum iron and ferritin levels showed a statistically significant reduction in Group I (p<0.01).…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…With respect to the startup values, the only factor that showed a statistically significant increase was serum ironbinding capacity. No statistically significant difference could be determined in other parameters [29]. In the present study, serum iron and ferritin levels showed a statistically significant reduction in Group I (p<0.01).…”
Section: Discussioncontrasting
confidence: 64%
“…It was determined that serum ferritin, iron level, and hemoglobin concentration decreases as pregnancy progresses in women who are not anemic and who do not take an iron supplement, even if adequate and balanced nutrition is provided [26,27]. Some studies have reported cases where, even if the pregnant patient was well nourished, the iron requirement could not be met without additional iron supplementation [28,29]. It has been established that patients who are not anemic at the start of their pregnancy and who are not given supplementary iron show normal iron levels 2 years after giving birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women who had anaemia in previous pregnancies tend to have persistent anaemia in the next pregnancy (Fleming et al, 1974), their low haemoglobin values being associated with low birthweight in the current pregnancy. Most women have inadequate iron stores to start with when they embark upon a new pregnancy (Puolakka et al, 1980;Romslo et al, 1983) and when their iron stores become deplete at the end of their pregnancy, they often do not have time to replenish their stores, which may take more than a year to return to prepregnancy levels (Letsky, 1995). The situation is made even worse with multiparity, and when the interval between pregnancies is too close for the women to recover her iron stores.…”
Section: Discussionmentioning
confidence: 99%
“…Also, even with iron deficiency, serum iron can be high or normal if the pregnant female is on oral iron. 10 The estimation of ferritin is expensive and cannot be routinely done in all, thus there is a need for surrogate markers to identify women who need iron supplementation. It is also necessary to determine the usefulness of red cell indices in diagnosing iron deficiency anaemia as well as subclinical iron deficiency longitudinally during the course of pregnancy.…”
Section: Introductionmentioning
confidence: 99%